Rapid immunochromatographic tests for the diagnosis of chronic Chagas disease in at-risk populations: A systematic review and meta-analysis. - Andrea Angheben; Dora Buonfrate; Mario Cruciani; Yves Jackson; Julio Alonso-Padilla; Joaquim Gascon; Federico Gobbi; Giovanni Giorli; Mariella Anselmi; Zeno Bisoffi (Public Library of Science (PLoS), 2019)
Background Despite of a high disease burden, mainly in Latin America, Chagas disease (CD) is underdiagnosed and undertreated. Rapid diagnostic tests (RDTs) might improve the access to diagnosis. The aim of this study is to review the accuracy of commercially available RDTs used in field conditions for the diagnosis of chronic CD in populations at risk, in endemic and non-endemic countries. Methods/principal findings We undertook a comprehensive search of the following databases: PubMed, SCOPUS, LILACS (last up-date on the 01st July, 2017), without language or date limits. Non-electronic sources have been also searched. This review included clinical studies with cohort recruitment of individuals at risk of T. cruzi exposure, without age limits; adequate reference standards for the diagnosis of CD. We excluded case-control studies and those testing RDTs during acute CD. Data on test accuracies were pooled through a bivariate random-effects model. Only one index test was evaluated separately. Geographical area, commercial brand, disease prevalence, study size, and risk of bias were explored as possible source of heterogeneity. Values of sensitivity and specificity were computed to obtain summary positive/negative likelihood ratios, and summary diagnostic odds ratio. Ten studies were included on six different immunochromatographic RDTs. The pooled sensitivity and specificity of the RDTs resulted 96.6% (95% CI 91.3-98.7%) and 99.3% (95% CI 98.4-99.7%), respectively. Test accuracy was particularly good in endemic areas (98.07%/99.03% of sensitivity/specificity, respectively). One test (Stat-Pak) showed an overall sensitivity of 97% (95% CI 87.6-99.3) and specificity of 99.4% (95% CI 98.6-99.8). Conclusions/significance RDTs demonstrated to be sufficiently accurate to recommend their use for screening in endemic areas, even as stand-alone tests. This approach might increase the accessibility to the diagnosis. However, an additional confirmatory test in case of positive result remains a prudent approach.